Conceptions of the afterlife in early civilizations : universalism, constructivism, and near-death experience - Shushan, Gregory (Continuum advances in religious studies., 2009)
Gregory Shushan challenges post-modern scholarly attitudes concerning cross-cultural comparisons in the study of religions. In an original and innovative piece of comparative research, he analyses afterlife conceptions in five ancient civilisations (Old and Middle Kingdom Egypt, Sumerian and Old Babylonian Mesopotamia, Vedic India, pre-Buddhist China, and pre-Columbian Mesoamerica). These are considered in light of historical and contemporary reports of near-death experiences, and shamanic afterlife 'journeys'. "Conceptions of the Afterlife in Early Civilizations" is a significant stu